The Journal of Cardiopulmonary Rehabilitation and Prevention at 40 yr and Its Role in Promoting Preventive Cardiology: Part 2. Issue 4 (July 2020) - Franklin, Barry A.; Brubaker, Peter; Harber, Matthew P.; Lavie, Carl J.; Myers, Jonathan; Kaminsky, Leonard A.
Abstract : Aggressive risk factor modification, including smoking cessation, blood pressure management, and more intensive efforts to control hyperlipidemia, as well as stress management training, are associated with improved cardiovascular outcomes and impressive mortality reductions. This commentary addresses these topics, with specific reference to lifestyle modification and complementary cardioprotective medications. Abstract : Individuals' risks for cardiovascular events are invariably tied to their exposure to major coronary risk factors. For many, assertive medical management can substantially lower these risks. This involves active prevention from medical practitioners and allied health professionals to promote smoking cessation, consideration of psychological factors, and adherence to pharmacotherapies as part of their routine patient counseling.